Going up the Andes: patterns and drivers of non-native plant invasions across latitudinal and elevational gradients - Fuentes-Lillo, Eduardo; Lembrechts, Jonas J.; Barros, Agustina; Aschero, Valeria; Bustamante, Ramiro O.; Cavieres, Lohengrin A.; Clavel, Jan; Herrera, Ileana; Jimenez, Alejandra; Tecco, Paula; Hulme, Philip E.; Nunez, Martin A.; et al. (My University, 2023)
The Andes mountain range in South America has a high level of endemism and is a major source of ecosystem services. The Andes is increasingly threatened by anthropogenic disturbances that have allowed the establishment of non-native plants, mainly in the lower elevation areas. However, synergies between climate change and anthropogenic pressure are promoting the spread of non-native plants to higher elevation areas. In this article, we evaluate and identify the main non-native plants invading Andean ecosystems, and assess their taxonomic families, growth forms and distribution patterns. Based on a systematic literature review, we identified the importance of climatic and anthropogenic factors as drivers of non-native species establishment in Andean ecosystems and the main impacts of non-native plants in the Andes. We then identified research gaps across each biogeographic region in the Andes. Finally, we highlight key elements to better tackle the problem of non-native plant invasions in Andean ecosystems, including the need for a systematic monitoring of invasion patterns and spread (e.g. MIREN protocol) and a common policy agenda across international borders for the prevention and management of non-native plants in this highly vulnerable region.
Keywords: non-native plants; andes mountain range; miren protocols; anthropogenic disturbance; invasive species prevention and management